APOE genotype and neuroimaging markers of Alzheimer's disease: systematic review and meta-analysis. Issue 2 (16th May 2014) - Liu, Ying; Yu, Jin-Tai; Wang, Hui-Fu; Han, Pei-Ran; Tan, Chen-Chen; Wang, Chong; Meng, Xiang-Fei; Risacher, Shannon L; Saykin, Andrew J; Tan, Lan
Abstract : Objective: We aimed to examine the association of apolipoprotein E (APOE) ɛ4 genotype with neuroimaging markers of Alzheimer's disease: hippocampal volume, brain amyloid deposition and cerebral metabolism. Methods: We performed a systematic review and meta-analysis of 14 cross-sectional studies identified in Pubmed from 1996 to 2014 (n=1628). The pooled standard mean difference (SMD) was used to estimate the association between APOE and hippocampal volume and amyloid deposition. Meta-analysis was performed using effect size signed differential mapping using coordinates extracted from clusters with statistically significant difference in cerebral metabolic rate for glucose between APOE ɛ4+ and ɛ4− groups. Results: APOE ɛ4 carrier status was associated with atrophic hippocampal volume (pooled SMD: −0.47; 95% CI −0.82 to −0.13; p=0.007) and increased cerebral amyloid positron emission tomography tracer (pooled SMD: 0.62, 95% CI 0.27 to 0.98, p=0.0006). APOE ɛ4 was also associated with decreased cerebral metabolism, especially in right middle frontal gyrus. Conclusions: APOE ɛ4 was associated with atrophic hippocampal volume in MRI markers, increased cerebral amyloid deposition and cerebral hypometabolism. Theses associations may indicate the potential role of the APOE gene in the pathophysiology of Alzheimer's disease.